Implementation of Simple Inhalation Steam Therapy in Children With Upper Respiratory Tract Infection - Solihin, Sopian (Universitas Pendidikan Indonesia, 2023)
The number of children suffering from Acute Respiratory Tract Infections (ISPA) is 59,417, and its prevalence is 40-80 times higher in developing countries compared to developed countries. The community service aims to implement simple inhalation techniques for children with ISPA and observe the nursing care response through a case study. The results show a positive response to airway cleanliness. The effectiveness of clearing the child's airway is indicated by a reduction in secretions and ronchi results in the lungs. Steam therapy with eucalyptus oil has a mucolytic effect (thinning mucus) and bronchodilating effect (relieving breathing).